VoIP Hacks - Wallingford, Theodore (O'Reilly, 2011)
Voice over Internet Protocol (VoIP) is gaining a lot of attention these days, as more companies and individuals switch from standard telephone service to phone service via the Internet. The reason is simple: A single network to carry voice and data is easier to scale, maintain, and administer. As an added bonus, it's also cheaper, because VoIP is free of the endless government regulations and tariffs imposed upon phone companies.